FATTY ACID CONTENT IN SANTANDEREANA GOAT MEAT ACCORDING TO AGE AT SLAUGHTER (@limentech, Ciencia y Tecnología Alimentaria, 2024)
The Santander goat is recognized and accepted as a pure breed and Colombian genetic heritage. It is production system is based on free grazing. The physicochemical and nutritional composition of it is meat is very little know. Therefore, the objective of this study was to determine the total fatty acids content in Santander goat meat according to the age at slaughter. For this purpose, Longissimus dorsi, Bicep femoris and Bicep brachi muscles of the left half carcass were obtained from 9 carcasses of 4, 8 and 14 months of age. The muscles were vacuum packed and stored refrigerated for 12 hours until analysis. The physicochemical characteristics and total fatty acid content were determined. Protein content increases with age at slaughter, with values above 19.5%. Fat content decreases with age at slaughter, with values below 3.0%. However, moisture content was not significantly affected by age. Saturated fatty acids were higher in Bicep femoris, Bicep brachi and Longissimus dorsi muscles (564.0; 347.6 and 250.8 mg/100 g of sample) from the age of 4 months than the other ages, followed by unsaturated and polyunsaturated fatty acids, respectively. Increasing age at slaughter significantly reduces the fat content of the meat and thus the fatty acid content.
Keywords: unsaturated acids; meat quality; goat meat; meat composition; polyunsaturated fats; saturated fats